2016
DOI: 10.1016/j.scitotenv.2015.12.072
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin, ergosterol, muramic acid and fungal DNA in dust from schools in Johor Bahru, Malaysia — Associations with rhinitis and sick building syndrome (SBS) in junior high school students

Abstract: This paper studied associations between ocular symptoms, rhinitis, throat and dermal symptoms, headache and fatigue in students by ethnicity and in relation to exposure to chemical microbial markers and fungal DNA in vacuumed dust in schools in Malaysia. A total of 462 students from 8 randomly selected secondary schools in Johor Bahru, Malaysia, participated (96% response rate). Dust was vacuumed from 32 classrooms and analysed for levels of five types of endotoxin as 3-hydroxy fatty acids (C10, C12, C14, C16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 45 publications
2
39
2
Order By: Relevance
“…The prevalence of weekly eye symptoms was 17.4%, higher than the 11.6% prevalence found in our previous school environment study in Johor Bahru, Malaysia (Norbäck et al, 2016a) and higher than the 6.5% prevalence of dry eye syndrome among adults in Singapore (Tong et al, 2009). In our study, the medians of SBUT and NIBUT were 14.8 and 12.2 s, respectively.…”
Section: Descriptive Data On Tear Film Stabilitycontrasting
confidence: 69%
See 2 more Smart Citations
“…The prevalence of weekly eye symptoms was 17.4%, higher than the 11.6% prevalence found in our previous school environment study in Johor Bahru, Malaysia (Norbäck et al, 2016a) and higher than the 6.5% prevalence of dry eye syndrome among adults in Singapore (Tong et al, 2009). In our study, the medians of SBUT and NIBUT were 14.8 and 12.2 s, respectively.…”
Section: Descriptive Data On Tear Film Stabilitycontrasting
confidence: 69%
“…We have previously demonstrated that there is an association between latitude and the level of indoor fungal DNA and the highest levels of moulds can be found in countries near the equator . In a previous school environment study from Johor Bahru, Malaysia, we found associations between total fungal DNA levels in schools and eye symptoms among the students, especially for the mould Aspergillus versicolor (Norbäck et al, 2016a). Moreover there was an association between the amount of fine dust in the classrooms and eye symptoms (Norbäck et al, 2016b).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…These can include EI and long-term sampling, e.g. of settled dust or pumped air, and use of total fungal analyses, such as for ergosterol, beta 1-3 glucan or total molds by the CAMERANEA method [21][22][23] or fungal DNA analysis via quantitative or qualitative polymerase chain reaction (PCR) [21][22][23][24].…”
Section: Targeted and Proportionate Approaches For Identifying And Momentioning
confidence: 99%
“…Environmental inspections (EIs) of mycological load have been suggested using a range of fungal-detection techniques, e.g. open Petri dish (OPD) versus active air sampling [19,20] and qualitative identification and quantitative monitoring of diverse fungal species and their mycotoxins [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%